Some inequalities for (s1;m1)-(s2;m2)-convex functions on the co-ordinates - Bai, Shu-Ping; Qi, Feng (Global Journal of Mathematical Analysis, 2013)
In the paper, the authors introduce a new concept “(s1;m1)-(s2;m2)-convex function on co-ordinates” and establish some inequalities for (s1;m1)-(s2;m2)-convex functions of 2-variables on the co-ordinates.